Sonography and multislice contrast tomography in the diagnosis of chronic venous insufficiency complicated by trophic ulcers - Kolomiets, O. (Journal of Education, Health and Sport, 2021)
Sonography has become the gold standard in the diagnosis of pathological changes in venous insufficiency, however, studies by other scientists indicate the need for a comprehensive study using phlebographic methods. The aim of the work was to compare the results of sonography and multislice tomography in the diagnosis of chronic venous insufficiency complicated by trophic ulcers. Materials and methods. The results of treatment of 97 patients with chronic venous insufficiency in stage C6 and C6r were evaluated. Ultrasound angioscanning of the venous system of the lower extremities at the planning stage of surgical treatment and in the postoperative period (early and after a year of observation) was performed on a digital device of expert class for cardiovascular studies (Toshiba Aplio 500) with 5-10 MHz sensor and appropriate standard software package examination of the venous system of the lower extremities. Multislice computed tomography was performed using X-ray computed tomography (Philips Brilliance 64). The study was performed using X-ray contrast iodine-containing medium (Omnipack-350) at the rate of 1 ml of the drug per kilogram of patient weight. Research results and their discussion. the sonographic study found that the causes of trophic ulcers were impaired venous blood flow in the veins of the lower extremities due to severe varicose transformation and decompensated reflux, and changes in the deep venous system due to thrombosis of the deep veins. Greater sensitivity and specificity of multislice computed tomography in the diagnosis of postthrombotic stenoses and obliterations were found compared with sonographic examination. This method is valuable in the study of the anatomy of the venous system, but does not allow to assess the parameters of hemodynamics (duration and degree of reflux, but only its presence).